Control growth of high density and morphological uniformity of taper-free Ni3Si2 NWs for enhancement in supercapacitor. (1st November 2022) - Ramly, Mohammad Mukhlis; Omar, Fatin Saiha; Chanlek, Narong; Aspanut, Zarina; Goh, Boon Tong
Highlights: High density and morphological uniformity of taper-free Ni3 Si2 nanowires. Solid-phase diffusion-control growth mechanism of Ni3 Si2 nanowires. High densely packed with thin, straight, and long morphologies of Ni3 Si2 NWs increase the redox active reaction sites. Large surface area of single crystalline Ni3 Si2 NWs electrode demonstrated a very high specific capacitance and excellent rate capability. Abstract: Lithium-ion batteries and supercapacitors unable to satisfy the growing energy needs of the world due to their distinct energy storage capacity and rate capability. Hence, asymmetric supercapacitor which can be another alternative of energy storage device however its performance greatly depending on the electrode materials. In this work, nickel silicide nanowires (Ni3 Si2 NWs) grown on Ni-coated Ni foam substrate via chemical vapor deposition technique. Structure and morphology studies revealed the material is a single-crystalline structure with the average NWs length and diameter of 12.5 ± 0.3 µm and 13 ± 2 nm, respectively, with a high the aspect ratio of 923. These physical characteristics are beneficial in asymmetric supercacitor as electrons are permitted to travel efficiently along each nanowire. In addition, the material has a large surface area (5.184 × 10 11 NWs/cm 2 ), thus, allowing high number of electrolyte ions to diffuse throughout the electrode to promote the redox reaction. Ni3 Si2 NWs and activated carbon are assembled into an asymmetric supercapacitor and the device exhibited a maximum specific capacity of 578.3 C/g and specific energy of 62.24 Wh/kg at specific power of 387.5 W/kg, and good cyclic stability with 76% capacity retention after 3, 000 cycles. Graphical abstract: Image, graphical abstract